Respostas
respondido por:
2
ponto A;
x= -2
y= 3
y=ax+b
3= -2a+b
ponto B
x= 6
y= 6
y=ax+b
6=6a+b
sistema de equações
-2a+b=3
6a+b= 6 .(-1)
-2a+b=3
-6a-b=-6
------------------------+
-8a= -3
a= 3/8
-2a+b= 3
-2.3/8+b=3
-6/8+b=3
b=3+6/8
b= 3+3/4
b= 15/4
equação
y=ax+b
y= 3/8.x+ 15/4
x= -2
y= 3
y=ax+b
3= -2a+b
ponto B
x= 6
y= 6
y=ax+b
6=6a+b
sistema de equações
-2a+b=3
6a+b= 6 .(-1)
-2a+b=3
-6a-b=-6
------------------------+
-8a= -3
a= 3/8
-2a+b= 3
-2.3/8+b=3
-6/8+b=3
b=3+6/8
b= 3+3/4
b= 15/4
equação
y=ax+b
y= 3/8.x+ 15/4
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás